Realization of the Zn3+ oxidation state. Issue 33 (13th August 2021) - Fang, Hong; Banjade, Huta; Deepika,; Jena, Puru
Abstract : Realizing the Zn +3 oxidation state by interacting with superelectrophilic clusters that are stable gas-phase trianions in their ground states. Abstract : Due to unfilled d-shells, transition metal atoms exhibit multiple oxidation states and rich chemistry. While zinc is often classified as a transition metal, electrons in its filled 3d 10 shell do not participate in chemical reactions; hence, its oxidation state is +2. Using calculations based on density functional theory, we show that the chemistry of zinc can fundamentally change when it is allowed to interact with highly stable super-electrophilic trianions, namely, BeB11 (CN)12 3− and BeB23 (CN)22 3−, which lie 15.85 eV and 18.49 eV lower in energy than their respective neutral states. The fact that Zn exists in +3 oxidation states while interacting with these moieties is evidenced from its large binding energies of 6.33 and 7.04 eV with BeB11 (CN)12 3− and BeB23 (CN)22 3−, respectively, and from a comprehensive analysis of its bonding characteristics, charge density distribution, electron localization function, molecular orbitals and energy decomposition, all showing a strong involvement of its 3d electrons in chemical bonding. The replacement of CN with BO is found to increase the zinc binding energy even further.